Development of magnetic fabrics with tunable hydrophobicity. Issue 4 (25th May 2013) - Ho, Thu; Ghochaghi, Negar; Tepper, Gary
ABSTRACT Polystyrene (PS) fiber mats incorporating iron (Fe) particles were fabricated by electrospinning and the hydrophobicity of the resulting magnetic fabrics was investigated with and without an applied magnetic field. The results show that the hydrophobicity increases in the presence of a magnetic field and the hysteresis in the advancing/receding contact angle decreases in the presence of a magnetic field. It is also shown that the contact angle and hysteresis increase with decreasing fiber diameter. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2352–2358, 2013